HAITI CRISIS AND THE OTTOMAN MERCHANTS IN THE EARLY TWENTIETH CENTURY GLOBAL ECONOMY (1903-1915) - Baycar, Kazim (BURHAN CAGLAR, 2023)
At the beginning of the twentieth century, social pressure against Ottoman Syrians emerged in Haiti, taking an immense part in the world agenda. Many countries directly or indirectly got involved in the crisis, which later turned out to be a political and economic collision between big powers. This study scrutinizes the Haiti crisis as a synopsis of the global economic competition and analyses it by focusing on the Syrians who were the victims of the situation. Haiti was a junction of the transatlantic trade route, and it possessed a very strategic location. The Ottoman Syrians who migrated to Haiti through the USA were among those who benefited themselves commercially from this positioning. The grasp of trade by Syrians drew the reactions among the Haitian administration and people. They were accused of causing inflation and unemployment. At the same time, big powers intended to intervene in the crisis under the guise of preserving the rights of Syrians. The Ottoman Empire did not hesitate to rescue its Syrian citizens from the turmoil. The article sketches out the Haiti crisis, which would become Western countries' display of power, relying on primary sources.
Keywords: Ottoman Empire; 19th Century; Haiti; Syrian Immigrants; Economic History; History